Pengaruh Shopping Lifestyle Dan Fashion Involvement Terhadap Impulse Buying Behavior Pada “Butik Kanabini” Di Tenggarong - Nilam Anggar Sari; Faridha Indrawati (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
Abstract :This research is meant to find out the influence of shopping lifestyle and fashion involvement to the impulse buying behavior. The population is the customers who have ever purchased clothes at Kanakbini Boutique Tenggarong. The sample collection technique has been done by using sampling purposive and 75 people have been selected as samples. The analysis has been done by using multiple linear regressions. The result of the research shows that shopping lifestyle have influence to the impulse buying of the fashion product at Kanakbini Boutique. Partially, Fashion Involvement has no significant effect to Impulse buying behavior of Kanakbini Boutique . Meanwhile, the variable which has dominant influence to the impulse buying is shopping lifestyle because its partial coefficient determination is the biggest when it is compared to other variables. The analysis using the coefficient of determination shopping lifestyle and fashion involvement simultaneously variable influence on impulsive buying by 29.3 % while the remaining 70.7% is the influence of other variables not examined in this study such as quality of service, brand, discount, display, hedonic shopping value, etc.Keywords: Impulse Buying Behaviour, Fashion Involvement, Shopping Lifestyle